Role of mother support group (KP-Ibu) on behavior of exclusive breastfeeding in work area primary health care (Puskesmas) of Ngoresan Surakarta - Nurrohmah, Anjar; Prawitasari, Shinta; Nisman, Wenny Artanty (International Journal of Research in Medical Sciences, 2017)
Background: Mother’s breastmilk (ASI) is the best food for babies. WHO recomended breastmilk for 6 month. Mother Support Group (KP-Ibu) is a program that has been established in the city of Surakarta to support IMD (Early Initiation of Breastfeeding) and exclusive breastfeeding. Puskesmas Ngoresan is one of the pilot project for the implementation of the KP-Ibu in Surakarta. Currently known achievements of exclusive breastfeeding in the puskesmas Ngoresan is 58%. The objective of the study was to identify the role of Mother Support Group (KP Ibu) on the behavior of exclusive breastfeeding in primary health Ngoresan of Surakarta. Methods: The study design was cross-sectional quantitative approach. The experiment was conducted in Puskesmas Ngoresan of Surakarta at November-December 2014. Sampling was done by purposive sampling. Subjects were mothers who had attended KP Ibu with children aged 6-24 months some 42 people. Data was collected using a questionnaire. Bivariate analysis using the chi-square test and multivariate analysis using logistic regression. Results: The Role of Support Group of mothers significantly affect the behavior of exclusive breastfeeding. KP Ibu who plays both have 12,85 times higher chance of the behavior of exclusive breastfeeding than women with Mother Support Group (KP Ibu) who did not play a role either. Possible contributions husband’s support and social support so affects the behavior of exclusive breastfeeding. Conclusions: The role of KP Ibu increased with the involvement of those closest around of the mother (husband, parents, family, co-workers and the public) to support the success of exclusive breastfeeding program.